Letter - Jeger, George
042-0056-001 SPANISH MEDICAL AID COMMITTEE President: Rt. Hon. LORD ADDISON Vice-Presidents: Dr. CHARLES BROOK. L C.C. Dr. DAVID FORSYTH VICTOR GOLLANCZ Professor JULIAN HUXLEY Rt. Hon. Sir WILLIAM JOWITT. K.C. Sir WALTER T. LAYTON The EARL OF LISTOWEL Miss MEGAN LLOYD GEORGE, MP. TOM MANN D.N. PRITT. K.C. M.P. Miss ELEANOR RATHBONE. M.P. Miss ESTHER RICKARDS. L.C.C. JOS. ROBINSON, M.D. Dr. MAUDE ROYDEN Sir ARCHIBALD SINCLAIR. MP. BEN TILLETT Dr JANET VAUGHAN ALFRED M. WALL Miss REBECCA WEST Chairman : Dr. H.B. MORGAN. M.D. Vice-Chairman: Dr. SOMERVILLE HASTINGS, L.C.C. Treasurers: Viscountess HASTINGS Professor J.R. MARRACK Viscount CHURCHILL Hon. Secretary: Mrs. LEAH MANNING, J.P. Organising Secretary: GEORGE JEGER, J.P. 24 NEW OXFORD STREET W.C.1 Telephone: HOLburn 1866 0605 May 10th 1938. Mr. Bell, T.U.C. Transport House, Smith Square, S.W.1. Dear Mr. Bell, I have now ascertained that the case of motor material required for the Vauxhall 1932 (chassis No. 6823) was despatched to Paris on April 28th, but has since been held up by the customs authorities in France. I am informed that Senor Santiago in Paris has been written to by the customs authorities regarding the duties and that they are awaiting his reply. l enclose a copy of the invoice. Yours sincerely, George Jeger Organising Secretary. 292/946/42/56